2006
DOI: 10.1002/app.23056
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer of dilute 1,2‐dimethoxyethane aqueous solutions during pervaporation process

Abstract: Pervaporation of 1,2-dimethoxyethane (1,2-DME) is evaluated by crosslinked oligosilylstyrene-poly-(dimethylsiloxane) composite membranes. A low flow velocity of the feed solution (1.0 L/min), corresponding to a Reynolds number of 220, is used. The pervaporation models are developed by combining the resistance in series and solution-diffusion models. The effects of the boundary layer on the performance of pervaporation are estimated by comparing experimental and theoretical data. The permeation fluxes of 1,2-DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…PDMS permeability to small organic molecules (i.e., solvents) has been predominantly investigated in the past by bulk methods. For example, the permeability of PDMS membranes can be explored by measuring their mass uptake in concert with the flux of a given solvent through the membrane. It has been shown that the diffusion of “good” organic solvents such as chloroform, toluene, and so forth through PDMS follows the expected Fickian behavior and exhibits an increase in the diffusion coefficient with solvent uptake . In contrast, poor solvents and solvent mixtures usually exhibit much more complex behavior reflective of different solvent-matrix interactions .…”
mentioning
confidence: 99%
“…PDMS permeability to small organic molecules (i.e., solvents) has been predominantly investigated in the past by bulk methods. For example, the permeability of PDMS membranes can be explored by measuring their mass uptake in concert with the flux of a given solvent through the membrane. It has been shown that the diffusion of “good” organic solvents such as chloroform, toluene, and so forth through PDMS follows the expected Fickian behavior and exhibits an increase in the diffusion coefficient with solvent uptake . In contrast, poor solvents and solvent mixtures usually exhibit much more complex behavior reflective of different solvent-matrix interactions .…”
mentioning
confidence: 99%